PENGARUH EKSTRAK ALOE VERA TEHADAP KEKUATAN TARIK KULIT PASCA INSISI (Penelitian Eksperimental pada Tikus Wistar) - , Dian Sekarsari, drg. Prihartiningsih, S.U., Sp. BM(K) ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Aloe vera is a natural ingredient that is widely used in wound healing post incision.Various studies have been conducted to determine the effectiveness of Aloe vera on the wound healing process but the timing of Aloe vera on the wound right after the incision in order to provide optimal resultsis not yet known . This study aims to determine the differences in tensile strength in the wistar ratskin samples treatedAloe vera extracts ascompared with controls seen at day 4th, 6th, 8th and 10th post incision. Fourty eight rats were divided into two groups: the non treated control group, and the treated group were applied with 0,5 ml Aloe vera extract topically twice a day arounds the area of incision. The incision was made on the back of rats with scalpel number 15 3 cm length reaches subcutane depth. The Flap was sutured interruptedly in three stitches. On day 4th, 6th, 8th and 10th respectively six rats of groups I and II, killed with ether, the stitches removed, skinned, and then performed a tensile strength test of the skin. Samples treated with Aloe vera showed increased tensille strength compared with control at 6th day. Statistical analysis with independent t test showed that there is significant differencis mean tensille strength between treated and control grup on 6th day (p<0.005), this result showed that the aplication of Aloe vera extract topically can increase the tensile strength of the wistar rats skin on day 6th post incision.